KESENJANGAN GENERASI ANTARA GURU & MURID SEBAGAI TANTANGAN DIGITALISASI PENDIDIKAN - Hani Ayu Rahmatiah; Nur Asiyah (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The technology development has been affecting all sectors in life, especially education. Most of all the countries in this world are empowering the use of high-technology tools in education, including Indonesia. There are sorts of policies made by the government to support the digitalization of education. Those are conducted to make Indonesia can compete to other countries in the Industry 4.0 Revolution era. While the goverment is trying to maxime the use of technology in education, we are faced by one big challege: the readiness of teacher to use the technology as a catalyst for the suceed of teaching and learning process. However, it is not an easy thing to do. There is a generation gap among today’s teachers as ‘digital immigrants’ and students as ‘digital natives’. This gap affects to their preception and process of adaptation to the technology. When the students can access all of the information they need to know without teacher, and teachers are having lack of digital literacy skills, those will cause sort of new problems in education, especially the obstruction of digitalization of education. So, as eduators, the today’s teacher should understand that their students have to master the technology, so do they.